THE INFLUENCE OF EMOTIONAL INTELLIGENCE AND PHYSICAL WORK ENVIRONMENT ON PERFORMANCE WITH MOTIVATION AS A MEDIATION VARIABLE AT SLBN PEMBINA PEKANBARU - Nur Lasera; Wulan Ayu Nurannisa; Iwandi Iwandi; Jumharroni Jumharroni (Jurnal Al-Iqtishad, 2025)
AbstractSLB Negeri Pembina Pekanbaru is an institution in the field of Special Education and Special Service Education (PKPLK) that handles students with physical, intellectual, mental, and sensory disabilities. To achieve organizational goals effectively and efficiently, attention must be paid to improving employee performance through emotional intelligence, work environment, and work motivation. This phenomenon relates to employee performance being influenced by emotional intelligence and the physical work environment, with work motivation serving as a mediating variable. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to employees and analyzed using the Structural Equation Modeling (SEM) method via the SmartPLS application. The population in this study consisted of 63 individuals, and a total of 63 samples were used (saturated sampling). The results showed that emotional intelligence and the physical work environment have a direct and significant effect on work motivation. Furthermore, emotional intelligence, physical work environment, and work motivation significantly affect employee performance. Work motivation is proven to mediate the relationship between emotional intelligence and employee performance, as well as between the physical work environment and employee performance. The implications of this study indicate that organizations/schools need to enhance emotional intelligence and create a comfortable physical work environment to boost work motivation and improve employee performance at SLB Negeri Pembina Pekanbaru.